춘란(Cymbidium goeringii )의 자매품종 그룹내 품종들 간의 유전적 친족성과 식별에 대한 연구 - 이경석(Kyung Suk Lee); 황정희(Jung Hee Hwang); 이대건(Dae Gun Lee); 정기화(Ki Wha Chung); 남다은(Da Eun Nam); 유진석(Jin Seok Yu); 노승우(Seung Woo Noh) (Weon'ye gwahag gi'sulji, 2021)
춘란(Cymbidium goeringii)에서 비슷한 지역에서 채취되고 유사한 표현형을 보이는 품종들을 서로 자매품종들로 흔히 불린다. 그런데, 자매품종들의 원 채집지나 채집자에 대한 정확하지 않은 경우가 많고, 서로 간의 유전적 근연성을 밝힌 연구는없었다. 본 연구는 자매품종들 간의 유전적 근친성에 대해 처음으로 조사하였다. 4 자매품종 그룹의 13 품종(358 시료)을 수집한 후 12 SSR의 유전자형을 multiplex PCR 방법으로 분석하여, 13 가지 복합유전자형을 분리하였다. 각 그룹에서 유래된 복합유전자형들의 계통도 분석과 형매 확률은 각 그룹을 구성하는 품종들이 서로 가까운 친척일 가능성을 시사하였다. 복합유전자형들은 품종-특이적인 경우도 있었지만, 일부는 그룹 내 여러 품종에서 동시에 관찰되었기 때문에, 자매 그룹내 품종들의 새로운 분류 기준의 확립이 요구되었다. 특히, 유사한 꽃의 특징을 보이면서 유전적 식별이 어려운 ‘홍노을’과 ‘루비’ 및 ‘노을’과‘세홍소’는 세밀한 표현형과 유전자형의 병행 분석을 통한 품종 별 정확한 식별 기준의 확립 및 품종 분류의 재정립이 필요하다고 판단된다. 본 연구는 춘란의 자매품종들의 근친 정도를 처음 밝힌 연구로서, 자매품종들의 유전적 본질에 대한 이해도를 높이고, 자매품종 명명의 재정립에 유용한 유전적 식별 기준을 마련하는데 도움을 줄 수 있을 것이다. Cultivars collected from similar regions and exhibiting similar phenotypes to each other arecommonly called sister cultivars in spring orchid (Cymbidium goeringii). However, no exactinformation is available for the original collection places and collectors of sister cultivars, and nostudy has revealed the degree of genetic relationship among them. This study was performed todetermine genetic kinship among sister cultivars. Thirteen flower-variant types of cultivarsconsisting of four sister cultivar groups (358 samples) were collected, and then thirteen combinedgenotypes were identified by the determination of 12 SSR genotypes using the multiplex PCR. Thephylogenetic analysis and the sibling probabilities of the combined genotypes suggested that thecultivars constituting each group were close relatives. Some combined genotypes were regarded tobe a cultivar-specific, but others were observed simultaneously in two or more cultivars within agroup. Therefore, it was suggested to establish a new classification criteria on the sister cultivars. Thisstudy particularly proposes to prepare a detailed evaluation criteria for cultivar pairs of ‘Hongnoeul’and ‘Ruby’, and ‘Noeul’ and ‘Sehongso’ in group-1 through exact co-analysis of the phenotypesand genotypes. As the first study on the genetic kinship between sister cultivars, this study will helpto understand the genetic nature of the sister cultivars, and to re-classify them. KCI Citation Count: 1